Surface roughness evolution to identify incubation time for hot corrosion of nickel-base superalloys: CMSX-4, CM247LC DS and IN6203DS at 550 °C - Chapman, Neil; Gray, Simon; Sumner, Joy; Nicholls, John R. (Springer, 2020)
In the absence of protective scales, nickel-base superalloys have an extremely limited hot corrosion incubation period before increased rates of attack are experienced. This paper reports on the nickel-base superalloys: CMSX-4, CM247LC DS and IN6203DS subjected to 550 °C hot corrosion exposures of durations ranging from 0 to 800 h, during which none of the superalloys developed a fully protective scale. The aim of the research was to identify the incubation period of each superalloy and this was achieved by means of surface roughness evaluations. A metrology exercise was performed on the cross section of test specimens which produced Cartesian data points which were subsequently converted to Ra and Rz data. Statistical analysis of the results suggested the incubation period lasted approximately 400, 500 and 200 h, respectively, for each superalloy. It was concluded that refractory metal phases within the microstructure were associated with the relatively short IN6203DS incubation period. This paper demonstrates that monitoring the changes in surface roughness provides a plausible method to identify the transition from incubation to propagation when studying 550 °C hot corrosion attack
Keywords: Selective oxidation; Solid state; Liquid sulphate